2011
DOI: 10.1371/journal.pone.0026594
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Phenotypes Resulting from a Mutagenesis Screen for Pharynx Muscle Mutations in Caenorhabditis elegans

Abstract: We describe a novel screen to isolate pharyngeal cell morphology mutants in Caenorhabditis elegans using myo-2::GFP to rapidly identify abnormally shaped pharynxes in EMS (Ethyl Methanesulfonate) mutagenized worms. We observed over 83 C. elegans lines with distinctive pharyngeal phenotypes in worms surviving to the L1 larval stage, with phenotypes ranging from short pharynx, unattached pharynx, missing cells, asymmetric morphology, and non-adherent pharynx cells. Thirteen of these mutations have been chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(56 reference statements)
3
9
0
Order By: Relevance
“…In addition, blmp-1 is important for pharynx and [40] male tail morphogenesis [41]. Under Nomarski optics, we confirmed the blmp-1 alae defect, as 40% of blmp-1(s71) mutants had incomplete alae and the rest had no alae in the adult stage (Figure S3C).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, blmp-1 is important for pharynx and [40] male tail morphogenesis [41]. Under Nomarski optics, we confirmed the blmp-1 alae defect, as 40% of blmp-1(s71) mutants had incomplete alae and the rest had no alae in the adult stage (Figure S3C).…”
Section: Discussionsupporting
confidence: 63%
“…In agreement with previous work in C. elegans (McKeown et al, 1998;Buechner et al, 1999;Norman and Moerman, 2002;Ferrier et al, 2011), we find that UNC-70/β is the dominant isoform in the spermatheca, with SMA-1/βH playing a restricted role. UNC-70/β is expressed throughout the spermatheca and SP-UT valve from L4 and into adulthood and loss of UNC-70/β results in a stronger reduction in spermathecal contractility compared with loss of SMA-1/βH.…”
Section: β-And β Heavy-spectrin Have Unique Expression Patterns and Csupporting
confidence: 93%
“…β heavy-spectrin has additional spectrin repeats, a SH3 proteinprotein interaction domain, and unique binding partners and functions (Médina et al, 2002;Lee et al, 2010b). UNC-70/β and SMA-1/βH have distinct expression patterns and subcellular localizations with the expression and function of SMA-1/βH restricted to a specific subset of tissues (McKeown et al, 1998;Buechner et al, 1999;Norman and Moerman, 2002;Ferrier et al, 2011). However, mutations in SMA-1/βH enhance the UNC-70/β loss of function phenotype, indicating the two β isoforms have some overlapping functions (Norman and Moerman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a screen of 10,000 mutagenized haploid genomes yielded 83 mutants with abnormal pharynges. 113 Specific aspects remain to be understood in detail, including cell fusions 124 and the secretion and deposition of many extracellular components, including glycans, 125 specialized cuticle 126 and chitin. 12 One of the most pressing issues toward a better understanding of axon guidance in the C. elegans pharynx concerns the source and distribution of the guidance cues.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 111 , 112 The other identified mutant was a new allele of sma-1 , which encodes a β-spectrin important for pharyngeal muscle development. 113 – 115 A detailed analysis of several other mutants that also affect the properties of the pharyngeal muscles revealed that they impose mechanical constraints that shape the gland cells: mutations in such genes result in abnormal gland cell morphology, including formation of supernumerary branches and swellings suggestive of hypertrophy. This suggests that pharyngeal muscles act primarily to regulate expansion of the gland cells.…”
Section: Morphogenesis Of Individual Cellsmentioning
confidence: 99%